EVALUASI HASIL PELAKSANAAN PROGRAM PEMBERDAYAAN SISTEM KEWASPADAAN PANGAN DAN GIZI (SKPG) DAN PENANGANAN DAERAH RAWAN PANGAN DI KECAMATAN GODONG KABUPATEN GROBOGAN - Ulul Karima; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The food insecurity problem is a complex issue because it does not only concern about the availability of food itself. Adequate food supply does not automatically indicate the conditions of food security at individual and household level. This study aims to explain the results of implementation of empowerment program of Food and Nutrition Vigilance System (SKPG) and Food Insecurity Handling at Godong District Regency of Grobogan as well as finding out the challenges and bottlenecks during the implementation of the program. The method used in this research is descriptive-qualitative method. In this study, the author use William Dunn’s six criteria of evaluation: effectiveness, efficiency, adequacy, equalization, responsiveness, and accuracy. The author found out that the program cannot be run optimally because the implementation program without need assessment. The program also did not meet the criteria of adequacy because the results of the program have not been able to solve the food insecurity problem, which proven by the increasing number of pre-prosperous family as much as 11.33% in 2015. Achieving equalization is yet not optimal indicated by minimal participation of groups inactivities carried out by BKP Grobogan. On the criteria of responsiveness, the program is not yet well assessed, which the needs of the target groups are not in accordance with the requirements. The accuracy of this program is also seen minimal because the target groups which are expected to have side business apparently not all of them has one.